2022
DOI: 10.3389/fmicb.2022.1064328
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of Bacillus subtilis or antibiotics modified intestinal microbiome of weaned pigs under enterotoxigenic Escherichia coli infection

Abstract: Our previous research reported that supplementation of Bacillus subtilis DSM 25841 promoted growth and disease resistance of weaned pigs under enterotoxigenic Escherichia coli (ETEC) challenge and its efficacy is comparable to carbadox. This follow-up study aimed to characterize the effects of ETEC infection, supplementing B. subtilis DSM 25841 or carbadox on intestinal microbiota of pigs. Forty-eight weaned pigs (6.17 ± 0.36 kg BW) were randomly allotted to one of four treatments: negative control (NC), posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
(73 reference statements)
1
3
0
Order By: Relevance
“…Bacillus has a variety of probiotic functions, similar to Bacillus amyloliquefaciens and Bacillus subtilis, which are widely used as probiotics in animal husbandry (Jiang et al, 2022;. Bacillus can induce Oscillospira to become a dominant genus (Keerqin et al, 2021) and can be used to treat diarrhea in pigs (Jinno et al, 2022). In this experiment, Bacillus was positively associated with growth performance, serum protein content, and antioxidant level, and negatively associated with serum fat and TC, as consistent with previous studies.…”
Section: Can Improvesupporting
confidence: 89%
“…Bacillus has a variety of probiotic functions, similar to Bacillus amyloliquefaciens and Bacillus subtilis, which are widely used as probiotics in animal husbandry (Jiang et al, 2022;. Bacillus can induce Oscillospira to become a dominant genus (Keerqin et al, 2021) and can be used to treat diarrhea in pigs (Jinno et al, 2022). In this experiment, Bacillus was positively associated with growth performance, serum protein content, and antioxidant level, and negatively associated with serum fat and TC, as consistent with previous studies.…”
Section: Can Improvesupporting
confidence: 89%
“…However, the lack of clustering in the stool samples from both groups suggests that the impacts of ETEC or B. subtilis HH2 on fecal microbial community composition may be limited, or that commercial dog food could also have influenced the fecal microbial community composition. Similar to studies on weaned pigs, alpha and beta diversity analyses also suggest that dietary supplementation of B. subtilis has a limited impact on the fecal microbiota in fecal samples [ 18 ]. The composition and structure of gut microbes in animals vary during different developmental stages, highlighting the lack of rigor in comparing fecal microbiota at different time points in this study.…”
Section: Discussionmentioning
confidence: 72%
“…An overabundance of Proteobacteria has been linked to dysbiosis in individuals who have metabolic or inflammatory conditions [ 63 ]. Moreover, previous studies have shown that the ETEC challenge increased the abundance of Proteobacteria and Firmicutes, and reduced the abundance of Bacteroides [ 18 , 64 ]. Similarly, in the dogc group, we observed a significant increase in the relative abundance of Firmicutes and a decrease in the relative abundance of Bacteroides in the stool at 24 h after the oral administration of ETEC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beta diversity measured post-weaning revealed a significant shift in the community ( P < 0.05), which may be attributed to the increased intake of GOS. In a study observing the effects of Bacillus subtilus or antibiotics on the piglet microbiome, they found that sampling site was the biggest influencer of shifts in beta diversity, but probiotic and antibiotic supplementation also shifted microbial communities [ 46 ]. This is comparable to the results we observed, where NG+ pigs differentiated from NG– pigs.…”
Section: Discussionmentioning
confidence: 99%